2017
DOI: 10.1097/eja.0000000000000636
|View full text |Cite
|
Sign up to set email alerts
|

Training in intraoperative handover and display of a checklist improve communication during transfer of care

Abstract: BACKGROUNDHandovers during anaesthesia are common, and failures in communication may lead to morbidity and mortality.OBJECTIVESWe hypothesised that intraoperative handover training and display of a checklist would improve communication during anaesthesia care transition in the operating room.DESIGNInterventional cohort study.SETTINGSingle-centre tertiary care university hospital.PARTICIPANTSA total of 204 random observations of handovers between anaesthesia providers (residents and nurse anaesthetists) over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…Coorte; Prospectivo ou etiologia-N2 Jullia et al, 2017 Antes do treinamento e com a implementação de uma lista, as pontuações nos grupos intervenção e controle foram semelhantes. Com a intervenção a pontuação aumentou e a melhora persistiu por meses e sem aumento da duração das transferências.…”
Section: Id Resultados/conclusãounclassified
“…Coorte; Prospectivo ou etiologia-N2 Jullia et al, 2017 Antes do treinamento e com a implementação de uma lista, as pontuações nos grupos intervenção e controle foram semelhantes. Com a intervenção a pontuação aumentou e a melhora persistiu por meses e sem aumento da duração das transferências.…”
Section: Id Resultados/conclusãounclassified
“…Jullia M, Tronet A, Fraumar F, et al Training in intraoperative handover and display of a checklist improve communication during transfer of care: an interventional cohort study of anaesthesia residents and nurse anaesthetists. Eur J Anaesthesiol, 2017, 34:471 [9].…”
Section: Resultsmentioning
confidence: 99%
“…10,20,26 Agarwala et al 10 reported that checklist adoption and use increased from 60% to 74% of intraoperative handoffs at 8 months after initial implementation. Similarly, Jullia et al 20 noted that the improvements in information scores persisted at 3 months postimplementation; however, other measures such as mean handoff duration and handoff documentation decreased at 3 months. Finally, Canale 26 reported that their checklist was integrated into the AIM system and was standardized into routine intraoperative handoff practice and presented at orientations for new clinicians.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Agarwala et al 10 described improvements with regard to discussion of intraoperative medications and fluid balance and improved item recall with their checklist. With handoff training and a 22-item checklist, Jullia et al 20 reported that the mean information transfer scores improved by 43% in the intervention group. Similarly, Lee et al 28 reported that information items spontaneously relayed increased from 54% to 98% with an electronic handover checklist and tutorial.…”
Section: Effects Of Handoff Tools On Outcomesmentioning
confidence: 99%